"Do We Believe in TripAdvisor?" Examining Credibility Perceptions and Online Travelers' Attitude toward Using User-Generated Content. (July 2013) - Ayeh, Julian K.; Au, Norman; Law, Rob
Recent press reports and complaints by hoteliers have called into question the credibility of travel-related user-generated content (UGC). Yet our understanding of the role of credibility perceptions in the context of UGC is limited, notwithstanding the rising interest in social media. Using an online survey of 661 travel consumers, this study applies the component-based structural equation modeling technique of partial least squares to examine online travelers' perceptions of the credibility of UGC sources and how these perceptions influence attitudes and intentions toward UGC utilization in the travel planning process. The model also draws on the theory of homophily to make predictions about the antecedent of credibility. Results validate the Source Credibility Theory in the context of UGC but also accentuate the central mediating role of attitude. In addition, the study finds support for perceptual homophily as a critical determinant of both credibility and attitude. Theoretical and managerial implications are highlighted.